Sub-optimal waypoints, UAV path planning and mosaicing application - Strubel, D. (Institute of Electrical and Electronics Engineers Inc., 2016)
Create a complete system of video surveillance using camera mounted on a robot like UAV to maintain optimized vast area coverage and reconstruct an image by using mosaicing techniques. This paper demonstrated the efficiency of using one UAV to cover vast area using optimized positions. Â© 2016 IEEE.